Python business intelligence cookbook : leverage the computational power of Python with more than 60 recipes that arm you with the required skills to make informed business decisions /: leverage the computational power of Python with more than 60 recipes that arm you with the required skills to make informed business decisions. (2015) - Dempsey, Robert
No abstract available